(untitled) (One Health & Risk Management, 2024)
Introduction. Antimicrobial Resistance (AMR) is one of the most serious threats to global public health, causing over 700 thousand deaths annually. In addition to the social burden, AMR generates high medical costs, and estimating these at the hospital level has been the subject of research in many international studies. Material and methods. A comprehensive study was conducted, encompassing 172 cases of invasive infections recorded in patients hospitalized at the “Timofei Mosneaga” Republican Clinical Hospital, from which strains of antimicrobial-resistant E. coli, K. pneumoniae, A. baumannii, and P. aeruginosa were isolated in the years 2019-2021. Based on data regarding the duration of hospitalization, treatment costs, and expenses for investigations, indicators such as average cost, the median, minimum and maximum values of treatment, including the cost of antibiotics and laboratory analyses, were calculated. Results. The economic impact indicators of AMR at the hospital level include: the duration of hospitalization, the total costs of a treated case, the costs of antibiotics, and the costs of laboratory analyses. In the structure of microorganisms isolated from the patients included in the study, K. pneumoniae predominates, accounting for 44.2%, and the total treatment cost for this organism was the highest at 202731.5 dollars. The maximum duration of hospitalization was recorded in patients from whom A. baumannii was isolated (27.7 days). Conclusions. The resistance of strains isolated from patients has directly contributed to the extension of the hospitalization period. The resistance of A. baumannii and K. pneumoniae species has predominantly led to the increase in the economic burden of AMR.